CARACTERIZACIÓN ESTADÍSTICA DE PESO, TALLA Y MEDIDAS DEL CORDÓN UMBILICAL DE UNA MUESTRA DE 100 NEONATOS EN PUEBLA MÉXICO - Haces y González, José Ramón; Rodríguez, David Espinosa; Oglesby, Juan Manuel López; Nuño de la Parra, José Pablo; Jiménez, Aurelio Horacio Heredia; Pérez, Manuel González (European Scientific Journal, ESJ, 2014)
Objective. Calculate statistical parameters and variables, concerning the weight, size and umbilical cord measures taken from 100 infants, 48 female and 52 male, to create standard curves are used to predict genetic disease. Material and methods. Measurements under medical protocol in 100 newborns in the hospital Spanish Beneficence of Puebla it performed. Umbilical cords it measured with a fiberglass tape, medical use for this work and in a time of less than ten minutes after delivery. Results. The calculated values of the measures of central tendency are very similar. The kurtosis and asymmetries it varied, but very close to the standard normal curve. Conclusions. Data from samples taken from 100 infants obey the normal curve shows both male and female.